Weekly time spent in the standing position is independently related to a better quality of life in postmenopausal women. (April 2016) - Diniz, Tiego A.; Neves, Lucas M.; Rossi, Fabricio E.; Fortaleza, Ana Claudia de S.; Rosa, Clara Suemi; Tebar, William Rodrigues; Christofaro, Diego G. Destro; Freitas-Junior, Ismael F.
Abstract: Objectives: To analyze the relationship between standing, sitting and reclining behaviors and quality of life in postmenopausal women. Study design: Cross-sectional study composed of forty postmenopausal women (aged 59.58 ± 5.32) who do not practice regular physical exercise. Body composition was measured using Dual-energy X-ray absorptiometry and quality of life by the Short Form 36 Health Survey (SF-36). Physical activity level was assessed using an accelerometer (Actigraph GTX3x) and is reported as minutes per week of moderate-to-vigorous physical activity (MVPA). Inclinometer analysis was also measured using this accelerometer model and reported as a weekly percentage of time spent standing, sitting and reclining. All analyses were performed using SPSS 17.0 software with the significance level set at 5%. Results: The percentage of time in the standing position was lower among women with poor quality of life ( p  < 0.05). Adjusted analysis (age, years since menopause, percentage of fat mass, MVPA and occupation status) was used to evaluate the relationship between quality of life and accelerometer inclinometer measures. The relationship between time standing and general health status ( β  = 0.353; 95%CI = 0.017; 0.377), social function ( β  = 0.429; 95%CI = 0.060; 0.396) and overall score ( β  = 0.336; 95%CI = 0.015; 0.442) were statistically significant. The relationship between the reclining position and both overall score ( β  = −0.320; 95%CI = −0.492; 0.006) and emotional aspects ( β  = −0.337; 95%CI = −0.191; 0.001) showed a tendency to present statistical significance. Conclusion: In summary, our results suggest that postmenopausal women who spend more time in the standing position have a better overall quality of life regardless of confounders.